The Differential Diagnosis of Central Nervous System Tumors: A Critical Examination of Some Recent Immunohistochemical Applications - Edgar, Mark A.; Rosenblum, Marc K. (Archives of pathology & laboratory medicine (1976), 2008)
Context.—As we write, novel antibodies that may well alter the routine practice of surgical neuropathology are in development, characterization, and the early stages of clinical use. These will be used for purposes of tumor subclassification, as prognostic markers, as identifiers of potential therapeutic targets, and as predictors of treatment response. Objective.—To provide for nonspecialists a critical assessment of the peer-reviewed literature (necessarily colored by our own experience) as it pertains to several immunohistochemical reagents that have been recently forwarded as adjuncts to the histologic typing of central nervous system tumors. Data Sources.—We address in these pages only antibodies that are commercially available, that have been the subjects of multiple published series, and that we have had occasion to use in the course of everyday problem solving. Conclusions.—Discussion concentrates on the use of 4 antibodies: BAF47 in the diagnosis of atypical teratoid/ rhabdoid tumor, OCT4 in intracranial germinoma, β-catenin in craniopharyngioma, and NeuN as a marker of neuronal differentiation in neuroepithelial neoplasms.